Materials from XIII Conference of Polish Association of Neuropathologists Warszawa, May 12-14, 2005 Original article The diagnosis and therapy of brain tumours - Nowak, Stanisław; Zukiel, Ryszard; Barciszewska, Anna-Maria; Barciszewski, Jan (Folia Neuropathologica, 2005)
Neoplasms arising from glial cells make up the most common group of primary brain tumors. The clinical outcome, especially the survival rates of the patients with brain tumours depend on tumour grade expressing its malignancy. A prognosis for glioblastomas (WHO IV) is very poor, but for astrocytomas (WHO I and II) it is relatively favourable. For oligodendrogliomas a longer survival time than for glioblastomas is observed. There is evidence that oxidative stress and reactive oxygen species (ROS) are crucial in the etiology and progression of a number of human diseases, including neoplasms. An oxidative damage of DNA, lipids and proteins is caused mainly with hydroxyl radical (•OH), the most reactive ROS species and may be seriously deleterious. In addition to all four basic nucleotides: adenosine (A), guanosine (G), tymidine (T) and cytosine (C), 5-methylcytosine (m5C) is a rare but normal component of cellular DNA and occurs mainly within a sequence of a structural gene or in regulatory regions. In the reaction with hydroxyl radical all DNA components can be modified, but m5C is relatively easily deaminated to thymine, which, in turn, pairs with adenine and after a round of replication, CG to TA transition occurs. Because thymine is a normal DNA base, therefore the product of spontaneous deamination of m5C is not so easily detected by cell\'s DNA repair system. Thus, 5-methylcytosine residue constitutes a mutational hotspot and DNA methylation pattern in patients might be useful as a primary diagnostic tool or as a marker for early detection of relapse of the disease. In recent years a new mechanism of posttranscriptional gene silencing has been discovered and named RNA interference (RNAi). This phenomenon is based on mRNA degradation mediated by small double-stranded RNA molecules, approximately 19-28 nucleotides in length, called short interfering RNAs (siRNAs). These molecules are produced from long dsRNAs by a dsRNA-specific endonuclease (DICER) and form 300 kD multi-enzyme complex (RISC) which by Watson-Crick base-pairing of noncoding strand with their mRNA-targets induce specific degradation. The high sequence-specificity of RNAi makes it a new, promising tool in a gene-function analysis as well as in potential therapeutics development.